2014
DOI: 10.1016/j.ijcard.2014.06.036
|View full text |Cite
|
Sign up to set email alerts
|

Impact of short-term mechanical circulatory support with extracorporeal devices on postoperative outcomes after emergency heart transplantation: Data from a multi-institutional Spanish cohort

Abstract: Patients bridged to emergency HT on short-term MCS are exposed to an increased risk of postoperative complications and mortality. In our series, preoperative bridging with VA-ECMO resulted in comparable post-transplant outcomes to those of patients transplanted on conventional support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 19 publications
2
12
0
3
Order By: Relevance
“…However, the total duration of the RRT had a median of 15 days, which is similar to previous reports . The reason could be that a high percentage of HT carried out at our center are in an emergency status, and it has been demonstrated that patients bridged to emergency HT on short‐term MCS are exposed to an increased risk of postoperative complications …”
Section: Discussionmentioning
confidence: 99%
“…However, the total duration of the RRT had a median of 15 days, which is similar to previous reports . The reason could be that a high percentage of HT carried out at our center are in an emergency status, and it has been demonstrated that patients bridged to emergency HT on short‐term MCS are exposed to an increased risk of postoperative complications …”
Section: Discussionmentioning
confidence: 99%
“…We avoid performing HTx directly from short-term support, because such patients are exposed to an increased risk of postoperative complications and mortality. 20,21 Instead, we have adopted the policy to convert these patients to long-term devices and list them first after end-organ recovery, rehabilitation, and home discharge. A high proportion of our patients receiving durable MCS receive implants from INTERMACS levels 1 or are converted from a short-term assist.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 We have limited experience regarding extracorporeal support for bridge to urgent heart transplant. However, our patients were successfully transplanted after support with VA-ECMO.…”
Section: Discussionmentioning
confidence: 99%